Spatiotemporal distribution of fish eggs and larvae in the Huanghe (Yellow) River estuary, China in 2005–2016 - Song, Yingfei; Zhang, Longjun; Luo, Xianxiang (Journal of oceanology and limnology, 2019)
Decreasing fish resources in estuaries is a subject of anthropogenic activities. Studies of the spatiotemporal distribution of fish eggs and larvae can help identify the status and processes underlying recruitment in a fishery. As the fifth largest river estuary in the world, the Huanghe (Yellow) River estuary (HRE) is a typical estuary that has been seriously affected by human activities. Annual surveys on ichthyoplankton and environmental factors were conducted in the months of May of 2005 and 2009–2016 in the HRE to investigate the spatiotemporal distribution of fish eggs and larvae and the associated influencing factors. A total of 23 and 20 species of eggs and larvae, respectively, were collected. The dominant orders were Perciformes (51.2%) and Clupeiformes (25.6%). The average number of fish species eggs and larvae were 6.0 and 4.1 in average abundance of 0.91 and 0.13 ind./m 3 , respectively. The dominant species were mainly low-commercial-value small-sized fishes, such as Clupanodon punctatus, Harengula zunasi , and Acanthogobius , whereas certain traditional commercial fishes, such as Trichiurus lepturus , and Clupea pallasii , were not seen. Analysis of the fish egg and larval community revealed four temporal assemblages and two spatial assemblages. Salinity was the main factor on the spatial distribution of ichthyoplankton communities, the species number and Shannon-Weiner diversity index ( H ′) of the fish egg and larval community near the river mouth with lower salinity were significantly lower than the community far away from the river mouth with higher salinity. In addition, increases of water temperature promoted the number and abundance of fish species eggs, and the areas of abundant prey tended to have a more diversified and abundant of ichthyoplankton species. In overall, overfishing, dam construction, and other human activities were the main drivers that led to the substantial decline in fishery resources in the HRE.